Exploring Novel Treatment Approaches for Post-Traumatic Stress Disorder - Murkar, Anthony (Université d'Ottawa / University of Ottawa, 2020)
Post-traumatic stress disorder is a disorder characterized by an inability to extinguish traumatic memories and heightened reactivity to emotional stimuli. Due to the heightened resistance of traumatic memories to extinction, treatment for PTSD has been challenging and is limited to behavioral therapies targeted at reducing responsivity to threatening stimuli. Currently there are no standard pharmacological interventions that are specific to PTSD; rather, drugs used appear to target symptoms of some of the co-morbid conditions, such as anxiety (e.g. benzodiazepines) or depression (antidepressants) - which may also affect fear-memory. In this thesis, we explore the effects of natural health products (NHPs) including naturally occurring peptides and some medical botanicals on fear memory in order to explore the efficacy of natural products as potential pharmacological targets for fear-based disorders. Fear-conditioning has been used effectively in both rodents and humans to study fear-learning. Fear-conditioning is a learning paradigm during which an unconditioned aversive stimulus (such as foot shock) is paired with a neutral stimulus (such as light or tone), such that the neutral stimulus becomes associated with aversion. Fear-learning has several well-characterized stages, including acquisition, consolidation, reconsolidation, expression, and extinction that can be manipulated in order to study the pharmacological action(s) on the attenuation of learned-fear. Blockade of reconsolidation, the state during which formed memories are briefly rendered susceptible to change following recall, may provide a window of opportunity to pharmacologically diminish learned fear. In Chapter 1 of the thesis, we discuss fear-conditioning as a pre-clinical model of PTSD to explore the effects of novel pharmacological treatments on the reconsolidation process in rodents. We ultimately hope to provide a framework for translational work in humans for attenuating conditioned responses to trauma-related stimuli among humans with PTSD. In Chapter 2, we present evidence that systemic administration of gastrin-releasing peptide attenuates the reconsolidation of conditioned fear in rodents. Similarly, in chapter 3, we explore the effects of Δ9-Tetrahydrocannabinol (THC) and Cannabidiol (CBD) on the reconsolidation of learned-fear, and provide evidence that cannabinoid molecules may similarly prove effective at blocking the reconsolidation of conditioned fear memories. In chapter 4, we present evidence demonstrating that extracts of medical botanical Souroubea sympetala and its components may similarly block reconsolidation of conditioned fear-memory, and also exert more general anxiolytic-like activity in the elevated plus maze paradigm. Finally, in chapter 5 a general discussion considers the relative therapeutic potential for future human clinical trials of each of the three tested groups of compounds.
Keywords: fear; anxiety; reconsolidation; ptsd; memory; souroubea; gastrin-releasing peptide; cannabis